Design of a Soil Nutrient Measuring Device for NPK (Nitrogen, Phosphorus, Potassium) Case Study of Cayenne Pepper Based on Arduino Nano V3 ATmega328P - Agil Soni Arafat; Ari Yuliati; R. Yovi Manova M (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2023)
Fertile soil electronic soil is essential for plant growth, and its quality significantly impacts crop yields. To help farmers measure the nutrient content of their soil more easily and accurately, innovative technology is required. In this case study, we present the design of a soil nutrient measuring device for Nitrogen, Phosphorus, and Potassium (NPK) that focuses on cayenne pepper. The device uses NPK sensors that can detect soil nutrients when inserted into the ground. The data collected by the sensors is sent to an ARDUINO Nano V3 ATMEGA328P, where it is processed and displayed as analog signals on a screen. The device can be customized according to the user's testing or cultivation needs, making it a useful tool for optimizing plant growth and crop yields.